America’s Failing Trade War With China: A Focus on Fentanyl - Hamilton, Corinna K. (American Journal of Trade and Policy, 2021)
As this article will explain in detail, much of the fentanyl reaching the hands of Americans comes from The People’s Republic of China (“China”). However, as seen by the rise in overdoses, most efforts to control the invasion of fentanyl have been unsuccessful. Although the federal and state governments have attempted to curtail this crisis by imposing sanctions and urging China to regulate production and shipping of the substance, fentanyl continues to flood the streets of the U.S. Moreover, the economic interdependence between the two nations complicates the matter. Because of this interdependence, the U.S. must take control of the situation. The U.S. fentanyl problem will persist if Americans are not dissuaded from using the drug. We must focus on the demand, rather than the supply. This comment focuses on the rise of opioids and synthetic pain relievers, and the variety of attempts at decreasing the number of addicts and overdoses. Initially, the comment will discuss the history of the popular drug opium, opiates, and prescription opioids, discussing state and federal attempts at curbing the crisis that the U.S. faces. It will address the rise of synthetic opioids, such as fentanyl, and how and why it was created. Section two will discuss how fentanyl and its precursors are imported into the U.S. from China. Section three will discuss U.S. federal and state attempts at legislation to control the flow of fentanyl into the U.S. Section four will address the implications, or perhaps fuel to the fire, that the influx in the supply of fentanyl from China has had on trade relations, and how the trade linkage between the two nations obfuscates the situation. The comment will conclude by hypothesizing how the U.S. and China will recalibrate their relationship and recommend that to combat the fentanyl emergency, the U.S. needs to take steps to offer Americans with drug addictions the assistance they need.
Keywords: trade; US-China relations; fentanyl; opioids; opioid epidemic